Influence of Gender on the Entrepreneurial Intention of University Students in Guayaquil (LACCEI, 2024)
Entrepreneurship is one of the main sources of income for developing countries, especially in Ecuador, where family businesses represent a large part of the country's economic entities. Therefore, this work analyzes the entrepreneurial intention in a sample of university students in Guayaquil, Ecuador, using the theory of planned behavior proposed by Azjen [5] as a theoretical model. The questionnaire used for data collection was based on the work of Liñan and Chen [4], from which 332 valid records were obtained. Subsequently, the influence of entrepreneurial attitude, perceived control and subjective norm on entrepreneurial intention was evaluated, through a structural equation model (SEM) specification considering the difference between men and women. The results showed that, although women have a greater willingness or attitude to undertake, they are limited by their low level of perceived control and high vulnerability to subjective norms. These results provide inputs for the promotion and promotion of entrepreneurship in specific groups according to their needs.